The Influence Of Brand Image And Brand Trust On Iphone User Loyalty (A Study On Iphone Users In Binjai City) - Ririn Pradilla Br Surbakti; Onan Marakali Siregar (UNIVED Press, 2026)
This study analyzes the influence of brand image and brand trust on iPhone user loyalty in Binjai City, Indonesia. In the era of digital transformation driven by Industry 4.0, the smartphone industry has experienced significant growth with increasingly intense competition. This research employs a quantitative approach with an explanatory design involving 100 iPhone users in Binjai City as respondents. Data were collected through structured questionnaires using a 5-point Likert scale and analyzed using multiple linear regression. The results show that brand image has a positive and significant influence on customer loyalty (β = 0.509, t = 4.337, p < 0.001), while brand trust does not demonstrate a significant effect (β = 0.077, t = 0.585, p = 0.560). Simultaneous analysis confirms that both variables together significantly influence customer loyalty (F = 16.741, p < 0.001) with the ability to explain 24.1% of loyalty variance. These findings indicate that in the context of established premium brands, brand image becomes the dominant factor in shaping loyalty, while brand trust functions as a supporting factor. This research provides theoretical contributions to the Theory of Reasoned Action and Social Identity Theory in digital marketing contexts, as well as practical insights for brand management strategies in emerging markets.